Proses Evaluasi pada Pembelajaran Daring di Sekolah Dasar - Huliatunisa, Yayah; Salsabillah, Salsabillah; Tantular, Lisa Damayanti; Hasri, Thalia Nindy; Nisaa, Khairun; Ramdhan, Fadlatul (Lembaga Yasin AlSys, 2022)
The purpose of this study was to review the evaluation process on online learning and the obstacles faced at SDS Plus Arrahmaniyah Serpong Utara, using a descriptive method with a qualitative approach. The sources of information for this research were one principal and two classroom teachers. Data collection techniques through observation, interviews, and documentation studies. The results of the data were analyzed using the theory of Miles and Huberman. The results of the study indicate that teachers are required to develop learning tools in accordance with the online learning process and government policies, seek to develop competence through technology and information capabilities, learn to use various evaluation methods and more innovative and creative learning through various activities such as workshops, discussions and sharing. sessions with colleagues. The impact of this research is increasing knowledge related to the level of creativity independence, learning experience and foresight in using technology tools for both teachers and students in the online learning evaluation process.